PENGARUH REMUNERASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI DI LINGKUNGAN DEPUTI BIDANG REHABILITASI BADAN NARKOTIKA NASIONAL - Agustina Massora dan Popi Alfadini (Fakultas Ekonomi Universitas Borobudur, 2015)
The results of this study, there is generally an influence between Remuneration and Discipline on Employee Performance in the Deputy Environment Sector Rehabilitation Agency National Narcotics. From multiple linear regression equation obtained Y = 4,407 + 0,990X1 + 0,071 X2. From the regression equation above it can be explained: Looks the constant value of 4.407. The value of the constant indicates that when the Remuneration and discipline variable is 0, the Performance score is 4.407. From the equation above is also known each regression coefficient is positive (0,990 and 0,071) so that describes the existence of direct effect between Remuneration and discipline on employee performance; where each increase of one variable score of Remuneration causes a performance increase of 0.990 and the increase of one disciplinary variable score increased by 0.071 at 4.407 constant. While the value of Beta coefficient, Remuneration has the highest value of coefficient Beta of 0.923 means the most dominant remuneration in determining the performance in the Deputy Environment Field Rehabilitation Agency National Narcotics. While Discipline has the value of Beta coefficient under Remuneration of 0.066 means the discipline determines Performance of employees in the Deputy of Rehabilitation of the National Narcotics Agency after Remuneration.From the results of F test calculations (simultaneously), F calculate of 314,037. While the probability value (Sig) in the F test is 0,000 smaller than 0.05, then Ho3 is rejected or Ha3 is accepted. So the conclusion is: there is a significant influence Remuneration and discipline together have an effect on to the performance of employees of Deputy BNN Rehabilitation Division. Keywords: Remuneration, Discipline and Performance